Keep on Guard Against Violent Communication (Verbal-Abuse) within Early Childhood Education - Afifah, Wiwiek (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2016)
This paper explores the forms of hardness in communication that occurs in early childhood education as well as trying to provide some alternative ways to escape from that violence. The form of violent communication done in schools is sneering, belittle, giving profanity, directly and excessively criticizing, threatening, painfully sarcastic, threatening, yelling, making scapegoats for problems that are not clear, scolding with redundancy, and blaming for something that children cannot do. The actions that can be used to prevent violent communication or verbal-abuse are teachers have to understand the children’ thoughts and feelings. When children are expressing their ideas, teachers must listen and give them a full attention. With those actions, teachers can bring a significant way to build compassionate, empathy, and quality of relationship among them.